2003
DOI: 10.1021/jp035189q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Hydrothermal Stabilities of Aged Periodic Mesoporous Organosilicas

Abstract: Methylene-, ethylene-, and phenylene-bridged periodic mesoporous organosilicas (PMOs) synthesized with nonionic alkylethylene oxide templates exhibited significantly better mechanical and hydrothermal stabilities than periodic mesoporous silica. Synthesis of PMOs utilized the acid-catalyzed hydrolysis and condensation of bis(triethoxysilyl) precursors around supramolecular polyoxyethylene(10) stearyl ether (Brij 76) templates. Nitrogen gas sorption, thermogravimetry, and X-ray diffraction have been used to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 27 publications
4
110
0
1
Order By: Relevance
“…The materials retain porosity and ordering after three consecutive reactions as can be seen from the nitrogen sorption and XRD data. These results also confirm the reported stability of Periodic Mesoporous Organosilicas [20,23]. Table 2 presents an overview of the chemical characterization of the solids after the different synthetic procedures.…”
Section: Characterization Of the Solidssupporting
confidence: 84%
“…The materials retain porosity and ordering after three consecutive reactions as can be seen from the nitrogen sorption and XRD data. These results also confirm the reported stability of Periodic Mesoporous Organosilicas [20,23]. Table 2 presents an overview of the chemical characterization of the solids after the different synthetic procedures.…”
Section: Characterization Of the Solidssupporting
confidence: 84%
“…16 Small signals at 29.8 ppm and 70.6 ppm arise from the surfactant residue. 7 Solid-state 29 Si MAS NMR results for this sample show overlapped peaks in the range of 250 ppm to 275 ppm, corresponding to T n silicon atoms [SiC(OH) n (OSi) 32n ] (Fig. 8b).…”
Section: Characterization Of Framework Composition By Xrf Ft-ir Nmrmentioning
confidence: 94%
“…It was found that the sulfonic acid-functionalized mesoporous organosilicas synthesized in this work show high catalytic activity and stability. It was shown by others [17,18] that PMOs exhibit very good mechanical and hydrothermal stability. These new materials could serve as solid acid catalysts with potential in many acid-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 97%